An Improved ANN Approach for Occupancy Detection of A Smart Building - Mitali Ray; Padarbinda Samal; Chinmoy Kumar Panigrahi (IAES Indonesian Section, 2023)
Building energy performance can be improved with a reduction in energy consumption. The heating and cooling loads of a building are important factors to consider in the field of energy conservation. It is possible to estimate energy consumption by predicting the presence of occupants in a room based on information provided by the HVAC (Heating, Ventilation, and Air Conditioning) system using standard information. Temperature, humidity, light, and CO2 levels from various sensors are taken as input parameters. In addition, the output of the network is programmed to be